Cadmium Concentrations in New Zealand Wheat: Effect of Cultivar Type, Soil Properties, and Crop Management. Issue 3 (1st May 2019) - Gray, Colin W.; Yi, Zicheng; Munir, Kiran; Lehto, Niklas J.; Robinson, Brett H.; Cavanagh, Jo‐Anne E.
Abstract : Wheat ( Triticum aestivum L.) grain is a contributing source of dietary Cd in New Zealand, but despite this, there is a dearth of information on Cd concentrations in wheat and the factors that affect uptake. We measured Cd concentrations in 12 wheat cultivars grown in field sites across New Zealand and also assessed the soil, plant, and crop factors that have been reported to affect Cd uptake. We found there was a wide range in grain Cd concentrations (0.004 to 0.205 mg kg −1 fresh weight [FW]). The overall mean concentration (0.066 mg kg −1 FW) was below the maximum limit (ML) of 0.1 mg kg −1 FW. Only 7% of grain samples across seven sites exceeded the ML. There were significant ( P < 0.05) differences (2.5‐fold) in Cd concentrations in wheat grain between cultivars. No strong significant relationships were found between soil properties and Cd concentrations in grain. Further, management factors affecting grain Cd concentrations were inconsistent. Given the lack of relationships between soils and management practices, the most effective way of limiting Cd uptake in wheat grain at sites where Cd exceeds MLs may be the use of low‐Cd‐accumulating cultivars. Further studies are required to explore specifically the influence of irrigation and effects of type and rate of fertilizer on Cd uptake in wheat, as well as to better understand the mechanisms of Cd uptake in wheat. Core Ideas: There was a 2.5‐fold range in Cd concentrations in grain among cultivars. No relationships were found between soil properties and Cd in grain. Overall Cd concentrations in wheat grain were below maximum limits. Using low‐Cd‐accumulating cultivars may be a strategy to limit uptake in grain.